2017
DOI: 10.1002/smll.201602770
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahedral DNA Nanostructure: A Potential Promoter for Cartilage Tissue Regeneration via Regulating Chondrocyte Phenotype and Proliferation

Abstract: Utilizing biomaterials to regulate the phenotype and proliferation of chondrocytes is a promising approach for effective cartilage tissue regeneration. Recently, a significant amount of effort has been invested into directing chondrocytes toward a desired location and function by utilizing biomaterials to control the dedifferentiation and phenotypic loss of chondrocytes during in vitro monolayer culture. Here, the transmission signals resulting from tetrahedral DNA nanostructures (TDNs) in the regulation of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
125
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(133 citation statements)
references
References 51 publications
(56 reference statements)
7
125
1
Order By: Relevance
“…liferation and promoting the migration of chondrocytes, TFNA, as a novel DNA material, can exhibit anti-inflammation and antioxidation activity in macrophages by suppressing the phosphorylation of members of the MAPK subfamilies. 21,22,41 Therefore, in this study, we aimed to explore how the combination of TFNA with wogonin affected inflammatory chondrocytes induced by IL-1β and inflamed knee joints in rats.…”
Section: S4mentioning
confidence: 99%
See 1 more Smart Citation
“…liferation and promoting the migration of chondrocytes, TFNA, as a novel DNA material, can exhibit anti-inflammation and antioxidation activity in macrophages by suppressing the phosphorylation of members of the MAPK subfamilies. 21,22,41 Therefore, in this study, we aimed to explore how the combination of TFNA with wogonin affected inflammatory chondrocytes induced by IL-1β and inflamed knee joints in rats.…”
Section: S4mentioning
confidence: 99%
“…[17][18][19][20] In terms of chondroprotective effect, we found that tetrahedral framework nucleic acid (TFNA), a specific, novel, and very promising DNA nanomaterial, can maintain the morphology of chondrocytes and enhance chondrocyte proliferation by activating the Notch signaling pathway and promote the migration of chondrocytes by activating the RhoA/ROCK signaling pathway at an optimum concentration of 250 nmol·L −1 . [21][22][23] TFNA can also be easily synthesized using several unique methods and specifically designed single-stranded DNA (ssDNA) by utilizing unique and sophisticated Watson-Crick base pairing. 24 Accumulating evidence has shown that TFNA but not ssDNA or other DNAs can permeate cells and enter mammalian cells via caveolin-mediated endocytosis, in which it remains intact for up to 48 h. Meanwhile, TFNA can escape from lysosomes via nuclear localization signals, which play a considerable and vital role in gene delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it was possible to ignore in this study, the surface morphology factor of the PDMS substrates of varying stiffness. Our group has tested the stiffness of PDMS substrates formulated with different ratios of base and curing agent (Zhang et al, , 2017. The stiffness of the PDMS substrates formulated with base to curing agent ratios of 10:1, 20:1, 30:1, and 40:1 was approximately 135kpa, 54kpa, 16kpa, and 6kpa, respectively.…”
Section: Zymographymentioning
confidence: 99%
“…In recent years, tissue engineering has been widely focused and considered an important approach to restore damaged tissues and organs. [1][2][3][4] The emergence of tissue engineering technology enables the successful isolation of dental pulp stem cells (DPSCs) and the use of DPSCs for repair of bone tissues or dentin-pulp tissue and even for the construction of natural teeth. [5][6][7][8] DPSCs are tissuespecific stem cells with a high proliferation rate, self-renewal capability and high accessibility.…”
Section: Introductionmentioning
confidence: 99%